2004
DOI: 10.1097/01.aog.0000137873.07820.34
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Blood Loss: Can Teaching Significantly Improve Visual Estimation?

Abstract: Error in estimating blood loss is dependent on actual blood loss volume. Medical students and experienced faculty demonstrate similar errors, and both can be improved significantly with limited instruction. This educational process may assist clinicians in everyday practice to more accurately estimate blood loss and recognize patients at risk for hemorrhage-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
2
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(178 citation statements)
references
References 21 publications
4
164
2
8
Order By: Relevance
“…Previous studies have shown that nurses are inaccurate visual estimators of emesis, with wide interparticipant variability (1-3). Experience has not been shown to improve the accuracy of estimations (2,3); the same trend was found for nurses and physicians when estimating blood volume (4,5).…”
mentioning
confidence: 80%
“…Previous studies have shown that nurses are inaccurate visual estimators of emesis, with wide interparticipant variability (1-3). Experience has not been shown to improve the accuracy of estimations (2,3); the same trend was found for nurses and physicians when estimating blood volume (4,5).…”
mentioning
confidence: 80%
“…In three studies (14)(15)(16), a total of 486 staff members of maternity services visually estimated blood loss in simulated scenarios before and after training courses. The three uncontrolled studies (14)(15)(16) show results in the same direction as the RCT.…”
Section: Training Courses On Estimating Blood Loss After Vaginal Delimentioning
confidence: 99%
“…Underestimation of blood loss at delivery time is one the reasons of the delayed diagnosis of blood loss. Many studies indicate that assessment of post-partum blood loss following a vaginal delivery is difficult and visual estimation of blood loss is frequently inaccurate [11][12][13] . Another method for measuring postpartum blood loss is calculated of Ht and Hb variations before and after…”
Section: Introductionmentioning
confidence: 99%